Microglia NLRP3 Inflammasomes Activation Involving Diabetic Neuroinflammation in Diabetic Mice and BV2 Cells - Li, Yuan; Zhang, Haifeng; Liu, Mingyuan; Guo, Weiying; Yu, Lu (Current Pharmaceutical Design, 2021)
Background: Hyperglycemia-induced microglia activation can cause a continuous release of proinflammatory cytokines, which gradually damages neurons and contributes to central diabetic neuroinflammation. Objective: This study aimed to illustrate the possible mechanism related to NLRP3 inflammasome and the aggravation of diabetes neuroinflammation. Methods: The targeted proteins from BV2 cells and brain tissues were tested by Western blot or immunohistochemistry. Cytokines from cell supernatant and serum were detected by ELISA. Meanwhile, cytoplasm and mitochondria ROS were determined by DCFHDA and Mito sox Red, respectively. Results: In vitro, BV2 cells were stimulated by different glucose concentrations (5.5 to 65 mM/L) above physiological values and maintained for different periods (12 to 48h). The proinflammatory cytokines IL-1β, IL18, IL6, TNFα and cytoplasm ROS were significantly increased in a dose-dependent manner, while mitochondrial ROS was unaffected. NLRP3 inflammasomes, MAPKs, and NF-ΚB pathways were obviously activated at the concentration of 35 mM/L for 12h. Inhibition assay using specific inhibitors indicated that the treatment of glucose (35 mM/L for 12h) could stimulate NLRP3 inflammasome activation via ROS/JNK MAPKs/NF-ΚB pathway. In STZ induced diabetes mice models, microglia NLRP3, ASC, and caspase-1 proteins were highly expressed, and serum cytokines IL-1β, IL6, IL18, and TNFα were remarkably increased. Conclusion: Microglia NLRP3 inflammasomes activation involves diabetic neuroinflammation in diabetic mice and BV2 cells via ROS/JNK MAPKs/NF-ΚB pathways.
Keywords: NLPR3